2018
DOI: 10.1186/s12986-018-0313-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of sex hormone-binding globulin with nonalcoholic fatty liver disease in Chinese adults

Abstract: BackgroundSex hormone-binding globulin (SHBG), a glycoprotein synthesized by hepatocytes, has been linked to insulin resistance and hepatic lipid metabolism and is suggested to be associated with nonalcoholic fatty liver disease (NAFLD). This study aimed to investigate the association of SHBG with NAFLD in Chinese adults.MethodsWe conducted a community-based, cross-sectional study in China involving 2912 participants aged 40–75 years old. All participants underwent detection for hepatic fat infiltration by ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…In addition, neither chain length nor saturation influenced substantially the relationship between long-chain FAs with SHBG or HNF4α mRNAs. These results extend the findings of Luo et al ( 29 ) and Sáez-Lopez et al ( 30 ), who reported that SHBG mRNA and protein levels correlate negatively with hepatic triglyceride content in patients with benign hepatic tumors or obese patients with NAFLD undergoing bariatric surgery, respectively, and suggest that down-stream signaling by increased hepatic fatty acids, rather than the fatty acid per se , is responsible for the low levels of SHBG in subjects with metabolic syndrome.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, neither chain length nor saturation influenced substantially the relationship between long-chain FAs with SHBG or HNF4α mRNAs. These results extend the findings of Luo et al ( 29 ) and Sáez-Lopez et al ( 30 ), who reported that SHBG mRNA and protein levels correlate negatively with hepatic triglyceride content in patients with benign hepatic tumors or obese patients with NAFLD undergoing bariatric surgery, respectively, and suggest that down-stream signaling by increased hepatic fatty acids, rather than the fatty acid per se , is responsible for the low levels of SHBG in subjects with metabolic syndrome.…”
Section: Discussionsupporting
confidence: 89%
“…Height, weight, waist circumference, and hip circumference were measured twice with the participants standing and wearing light daily clothing, and the mean values were calculated. Body mass index (BMI) was calculated as weight (kg) divided by the height squared (m 2 ), and values greater than 24 kg/m 2 were identified as overweight [25]. The waist-to-hip ratio (WHR) was calculated as the waist circumference divided by the hip circumference.…”
Section: Clinical and Laboratory Assessmentmentioning
confidence: 99%
“…NAFLD was diagnosed by abdominal ultrasonography following the standard criteria issued by the Fatty Liver Disease Study Group of the Chinese Liver Disease Association [25,26]. The remission of NAFLD was defined as the presence of NAFLD at baseline and the absence at the follow-up.…”
Section: Evaluation Of Nafldmentioning
confidence: 99%
“…[57,58] The SHBG level in the liver and peripheral was significantly lower in patients with hepatic steatosis, where serum SHBG was found to be negatively associated with insulin resistance and hyperinsulinemia. [59,60] SHBG level was also shown to be significantly lower in menopausal women patients with NAFLD verified by liver biopsy. After the normalization of age, waistline and BMI, SHBG was an independent risk factor for NAFLD.…”
Section: Sex Hormone-binding Globulinmentioning
confidence: 86%